A new sericomyiine flower fly from China (Diptera: Syrphidae) - Xie, Hongyan; Cunningham, Saul A.; Yeates, David K.; Thompson, F. Christian (Zootaxa, 2014)
A new species of flower flies is described from China (Sichuan & Yunnan: Hengduan Mountains), Sericomyia khamensis Thompson & Xie). A key is provided to the species of the subtribe Sericomyiina found in China along with nomenclatural and taxonomical notes on them.